2012
DOI: 10.1371/journal.pone.0047286
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem/Progenitor Cell Proliferation and Differentiation Is Differentially Regulated by High-Density and Low-Density Lipoproteins in Mice

Abstract: RationaleHematopoietic stem/progenitor cells (HSPC) are responsible for maintaining the blood system as a result of their self-renewal and multilineage differentiation capacity. Recently, studies have suggested that HDL cholesterol may inhibit and impaired cholesterol efflux may increase HSPC proliferation and differentiation.ObjectivesWe hypothesized that LDL may enhance HSPC proliferation and differentiation while HDL might have the opposing effect which might influence the size of the pool of inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 48 publications
9
71
1
Order By: Relevance
“…If the mechanisms remain to be identified, the potential discrepancy between our study and BM transplantation studies (16) may reside in a role of SR-BI in BMresident hematopoietic stem and progenitor cells (HSPC). Indeed, some recent data indicated that SR-BI might play a critical role in HSPC biology, notably in HSPC differentiation and proliferation in response to LDL and HDL (27,28). Moreover, we observed a trend for increased survival of CLP-treated hypomSR-BI; LysM-Cre mice, which would also not support a major protective function for SR-BI expressed in cells of myeloid origin.…”
Section: Discussioncontrasting
confidence: 72%
“…If the mechanisms remain to be identified, the potential discrepancy between our study and BM transplantation studies (16) may reside in a role of SR-BI in BMresident hematopoietic stem and progenitor cells (HSPC). Indeed, some recent data indicated that SR-BI might play a critical role in HSPC biology, notably in HSPC differentiation and proliferation in response to LDL and HDL (27,28). Moreover, we observed a trend for increased survival of CLP-treated hypomSR-BI; LysM-Cre mice, which would also not support a major protective function for SR-BI expressed in cells of myeloid origin.…”
Section: Discussioncontrasting
confidence: 72%
“…It has also been demonstrated that low-density lipids (LDLs) increase, whereas high-density lipids (HDLs) decrease HSC number (Feng et al, 2012;Murphy et al, 2011). In addition, hormones known to be elevated in obesity, such as leptin, may also increase HSC numbers as evidence by elevated numbers following exogenous application of this hormone to ex vivo cultures (Dias et al, 2013).…”
Section: The Impact Of Obesity On Stem Cell Functionmentioning
confidence: 99%
“…Nonetheless, it is possible that in addition to regulating ERα function, 27HC also influences HSCs through effects on bile acid biosynthesis. Our results offer a potential explanation for the long-standing observation that increased cholesterol levels are associated with increased HSPC mobilization in mice and humans (11)(12)(13)(14)(15)(16). 27HC levels increase as cholesterol levels increase (6).…”
Section: Discussionmentioning
confidence: 60%
“…Nonetheless, cholesterol is known to promote HSC proliferation and mobilization (11)(12)(13). Patients with hypercholesterolemia mobilize larger numbers of CD34 + cells following treatment with cyclophosphamide and granulocyte colony-stimulating factor (G-CSF) as compared with patients with lower cholesterol levels (14).…”
Section: Introductionmentioning
confidence: 99%